A Gallbladder Carcinoma Patient With Pseudo-Progressive Remission After Hydrogen Inhalation - Chen, Jibing (Onco Targets Ther, 2019)
BACKGROUND: Hydrogen therapy has been reported to convert exhausted programmed cell death receptor (PD-1)+CD8+ T cells to PD-1-CD8+ T cells, in advanced colorectal cancer patients, which is associated with significantly prolonged survival. CASE PRESENTATION: A 72-year-old female patient presented with metastatic gallbladder cancer and underwent symptomatic treatment combined with hydrogen therapy. The tumors were initially enlarged and displayed increased tumor marker expression following hydrogen inhalation therapy, after which they continued to remit, similar to the pseudo-progression that occurs after anti-PD-1 treatment. During one month of hydrogen therapy, the patient’s gallbladder and liver tumors continued to progress, and intestinal obstruction occurred. The intestinal obstruction was gradually relieved after symptomatic treatment, and the metastases in the abdominal cavity gradually decreased in size, anemia and hypoalbuminemia were corrected, and both the lymphocyte and tumor marker levels returned to normal. The patient was able to resume normal life two and a half months after hydrogen inhalation and survived over 10 months. CONCLUSION: This is the first report of pseudo-progression followed by sustained remission after hydrogen inhalation. This phenomenon is similar to the pseudo-progression-remission pattern that occurs following PD-1 antibody treatment. These findings suggest that hydrogen may have an inhibitory effect on PD-1 expression.